Covalent Linkages of Molecules and Proteins to Si-H Surfaces Formed by Disulfide Reduction - Dief, Essam; Vogel, Yan; Peiris, Chandramalika; Le Brun, A.P.; Gonçales, V.R.; Ciampi, Simone; Reimers, J.R.; Darwish, Nadim (AMER CHEMICAL SOC, 2020)
Thiols and disulfide contacts have been, for decades, key for connecting organic molecules to surfaces and nanoclusters as they form self-assembled monolayers (SAMs) on metals such as gold (Au) under mild conditions. In contrast, they have not been similarly deployed on Si owing to the harsh conditions required for monolayer formation. Here, we show that SAMs can be simply formed by dipping Si-H surfaces into dilute solutions of organic molecules or proteins comprising disulfide bonds. We demonstrate that S-S bonds can be spontaneously reduced on Si-H, forming covalent Si-S bonds in the presence of traces of water, and that this grafting can be catalyzed by electrochemical potential. Cyclic disulfide can be spontaneously reduced to form complete monolayers in 1 h, and the reduction can be catalyzed electrochemically to form full surface coverages within 15 min. In contrast, the kinetics of SAM formation of the cyclic disulfide molecule on Au was found to be three-fold slower than that on Si. It is also demonstrated that dilute thiol solutions can form monolayers on Si-H following oxidation to disulfides under ambient conditions; the supply of too much oxygen, however, inhibits SAM formation. The electron transfer kinetics of the Si-S-enabled SAMs on Si-H is comparable to that on Au, suggesting that Si-S contacts are electrically transmissive. We further demonstrate the prospect of this spontaneous disulfide reduction by forming a monolayer of protein azurin on a Si-H surface within 1 h. The direct reduction of disulfides on Si electrodes presents new capabilities for a range of fields, including molecular electronics, for which highly conducting SAM-electrode contacts are necessary and for emerging fields such as biomolecular electronics as disulfide linkages could be exploited to wire proteins between Si electrodes, within the context of the current Si-based technologies.